PENGENDALI ADAPTIVE NEURO FUZZY INFERENCE SYSTEM (ANFIS) UNTUK PENGATURAN KESTABILAN PADA SISTEM WARD LEONARD - ., Ricky Budi Setiawan Pinaria (Faculty of Engineering, Universitas Tanjungpura, 2018)
The development of control technology has progressed considerably from classical control to automatic controls to intelligent controls. ANFIS is Adaptive Neuro Fuzzy Inference System one of intelligent control techniques that are capable as well as human capabilities. In this study aims to test the ability of ANFIS controller on Ward Leonard system speed control. The design of ANFIS controller and Ward Leonard system to be tested using Matlab and Simulink on Matlab by collecting Maximum Overshoot data and Steady State time on Ward Leonard system condition without controller and with ANFIS Controller controller. Results Ward Leonard system without a controller takes 4.32 seconds for the main driving motors reach steady state and 2.013 seconds for the load motor can reach steady state. The unattended Ward Leonard system has a Maximum Overshoot value of 62.2% on the Main Movement Motor and 78.5% on the Load Motor. The Ward Leonard system with ANFIS controller with a unit feedback system on the main Move Motors can reach a steady state time of4,809 seconds and for the 5.55 seconds required by the Load Motor to reach the steady state. The Ward Leonard system with the ANFIS controller has Maximum Overshoot value of each of the main Driving Motor and the Motor load of 0.3%. Factors that cause steady state time of Ward Leonard system condition with ANFIS controller and condition of Ward Leonard system without controller is ANFIS controller which takes a relatively longer time to muffle error based on membership function of existing ANFIS controller. Keywords: ANFIS controller, Ward Leonard system, Maximum Overshoot, Steady State.